Teoria „transferu kulturowego” i jej zastosowanie w badaniach historii społecznej (na przykładzie polsko-włoskich kontaktów doby Risorgimento) - Jurek, Lidia (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2009)
So called relational approaches gain growing popularity among historians due to the multiplicity of new perspectives on history of societies they give. The credit goes especially to the following theories: comparative history, cultural transfer, histoire croisée and transnational history. The article brings closer above theories to the Polish readership and focusing on cultural transfer theory depicts possible ways of its use in the analysis of relations between Poland and Italy during the period of Risorgimento. In doing so, it contends that new interesting discoveries can be made with reference to the Italian influence on the Polish conceptions of the nation.